The Influence of Digital Platforms on Social Networks and Collective Action among Urban Youth - Nini Karlina Ahmad; Sarmedi Putra (Mahogany Journal De Social, 2026)
Digital platforms have become central to the social lives of urban youth, reshaping how social networks are formed and how collective action emerges in contemporary cities. This study aims to analyze the influence of digital platforms on social networks and collective action among urban youth, with a particular focus on the relational mechanisms that connect digital engagement to collective participation. A quantitative cross-sectional survey design was employed, collecting data from urban youth and analyzing the relationships between digital platform use, social network characteristics, and collective action using regression and mediation analysis. The results reveal that digital platform use is positively associated with larger, more diverse, and more connected social networks. These network characteristics significantly increase youth participation in collective action, both online and offline. Moreover, social networks partially mediate the relationship between digital platform use and collective action, indicating that digital platforms facilitate collective engagement primarily by strengthening relational structures rather than acting as direct mobilizing forces. The findings contribute to a more nuanced understanding of digitally mediated collective action by highlighting the central role of social networks in urban youth participation. The study underscores the importance of network diversity and connectedness for fostering inclusive and sustainable collective action in digitally mediated urban environments.